Evaluation of Risk Management Implementation in Import Duty Tariff Determination Based on Ministerial Regulation - Yanuar, Yos Ricki; Djakman, Chaerul Djusman (E-Jurnal Akuntansi, 2025)
The potential for shortfalls in state revenue and recurring findings in the Internal Control System indicate the existence of potential risks that have not been effectively managed. This study aims to assess the alignment of risk management implementation at XYZ Government Office with the applicable Ministerial Regulation on risk management practices. This study uses a qualitative case study method, data were gathered through triangulation of methods (documentation, interviews) and sources (key informants). The findings reveal that risk management is perceived merely as an administrative routine. Consequently, the entire process, including identification, analysis, evaluation, and mitigation, is not optimally implemented. This results in a failure to identify root causes and a tendency to underestimate true risk levels. Keywords: Risk Management; Import Duty; State Revenue; Public Sector